Palladium-Catalyzed Organic Reactions Involving Hypervalent Iodine Reagents - Samata E. Shetgaonkar; Ritu Mamgain; Kotaro Kikushima; Toshifumi Dohi; Fateh V. Singh (Molecules, 2022)
The chemistry of polyvalent iodine compounds has piqued the interest of researchers due to their role as important and flexible reagents in synthetic organic chemistry, resulting in a broad variety of useful organic molecules. These chemicals have potential uses in various functionalization procedures due to their non-toxic and environmentally friendly properties. As they are also strong electrophiles and potent oxidizing agents, the use of hypervalent iodine reagents in palladium-catalyzed transformations has received a lot of attention in recent years. Extensive research has been conducted on the subject of C—H bond functionalization by Pd catalysis with hypervalent iodine reagents as oxidants. Furthermore, the iodine(III) reagent is now often used as an arylating agent in Pd-catalyzed C—H arylation or Heck-type cross-coupling processes. In this article, the recent advances in palladium-catalyzed oxidative cross-coupling reactions employing hypervalent iodine reagents are reviewed in detail.